Utilization of metacognitive judgments in the allocation of study during multitrial learning. - Nelson, Thomas O.; Dunlosky, John; Graf, Aurora (Psychological Science., 1994)
A study was conducted to examine ways that an individual's judgments of learning (JOL) can be utilized when allocating additional study. The task analyzed was multitrial learning of Swahili-English translation equivalents by 228 undergraduates. The findings revealed how metacognitive monitoring can be employed to benefit multitrial learning. Computer-controlled allocation of restudy based on subjects' JOLs was equivalent to most subjects' own allocation of restudy, demonstrating that the computer algorithm can give a sufficient account of people's allocation of restudy. Computer-controlled allocation of restudy based on subjects' JOLs was more effective than a computer-controlled allocation based on normative performance, indicating that people's metacognitive monitoring of idiosyncratic knowledge has functional utility in causal chains for learning.